Estudo da estabilidade global em edifícios de concreto armado através dos parâmetros de instabilidade Gama Z e FAVt - Borges, Lana Mondadori Záquera (2017)
The evolution of the structures happened due to the growth of the cities and the appearance of new materials used in civil construction. The buildings now require more complex structural arrangements due to the verticalization and slenderness of the structures. As a consequence, the studies concerning the overall stability of buildings become important to ensure the safety of the structure, given the geometrical imperfections caused by the horizontal actions and the non-linearity of the structure. In this context, structural modeling software becomes an aid tool for engineers to obtain more refined calculations and close to reality, however, it is the engineer's responsibility to apply the correct data entry in these programs, as well as to perform the reading and interpretation of results accurately. This work aims to study the behavior of global stability of buildings through the instability parameters which is presented in NBR 6118 (ABNT, 2014) and FAVt which is a specific parameter of CAD / TQS software. For this study, different modeling of a building in the CAD / TQS Software was carried out. From the results obtained it was possible to demonstrate the behavior of the instability parameters in relation to the adoption of the different characteristics used in the modeling. Also, in order to demonstrate the use of the parameters to obtain global second-order effects, the second-order global effects were verified in four columns of the building.